Economic Optimization of Offshore Petroleum Development - Frair, Les; Devine, Mike (Management Science, 1975)
Due to shortages in crude oil supplies there is considerable motivation to develop the vast petroleum resources located on our outer continental shelf. Offshore oil operations require great outlays of capital, and this paper presents a model and solution procedure for optimizing the economics of developing a given offshore field. The model considers the following variables: (1) How many offshore drilling platforms are needed? (2) How many wells should be drilled from each platform? (3) What is the location of each platform? (4) From which platform should each well be drilled? (5) What are the time schedules for placing the platforms and drilling the wells? (6) What is the production schedule for each reservoir? The objective of this model is the maximization of discounted after-tax cash flows subject to production limiting constraints. Because of the nonlinear nature and size of this model for realistic problems, it is decomposed into sub-models for which effective solution procedures are developed. Computational results are presented for two example problems.